Peran Akuntansi Manajemen dalam Penyusunan Anggaran dan Pengendalian Biaya Operasional pada Jasa Fotografi Ethicvisual Jombang - Nisrina Nabihah Ramadhani; Vanesa Tri Suprianingrum; Ridho Fafero; Ilham Dwi Adeyansyah; Adhit Rizqullah Dzikra (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This research examines the role of management accounting in budgeting and controlling operational costs at Ethicvisual photography services in Jombang. Management accounting is an internal accounting system designed to meet the information needs of managers in the company. Relevant accounting information is very important for managers to carry out planning, control, and decision-making functions. Cost analysis through the calculation of cost per unit can be used as a basis for performance measurement and budgeting. This research uses a qualitative descriptive approach with data obtained from scientific journal articles and field data through observation, interviews, and documentation. The results showed that management accounting plays an important role in helping photography service companies manage finances, make the right decisions, and achieve operational efficiency.